PENGEMBANGAN LKPD BERBASIS SAINTIFIK TERINTEGRASI AYAT AL-QUR'AN PADA MATA PELAJARAN IPAS KELAS IV SD - Rasyidah Muslim, Putri; Sunarti; Rahmat Umara, Alifiyoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the results of the analysis of the needs of teachers and students, which indicate that they have not yet been able to develop students' understanding of natural and social phenomena holistically. However, in practice, there are still various obstacles in IPAS learning, especially in fostering students' critical and scientific thinking skills. One of the problems often encountered is the lack of teaching materials that can produce scientific concepts with religious values, particularly from an Islamic perspective. The purpose of this research is to develop a scientific-based Student Worksheet that integrates verses from the Qur'an. The type of this research is Research and Development (R&D) using the 4D model, which includes Define, Design, Develop, and Disseminate. The data collection technique used is the Validity Questionnaire and the Practicality Questionnaire. The results of this study indicate that the LKPD developed based on the results from validators 1, 2, and 3 are categorized as very valid with a total score of 98%, and the results of the teacher practicality test are categorized as very valid with a total score of 100%, while the results of the student practicality test are categorized as very valid with a total score of 99%. Based on this, it can be concluded that the Scientific-Based LKPD integrated with Quranic verses in the IPAS subject for 4th grade elementary school is categorized as valid and practical.